THE SYNTACTIC FUNCTIONS AND COMPARATIVE ANALYSIS OF THE PAST TENSE VERB IN ARABIC AND UZBEK LANGUAGES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides a comparative analysis of the morphological structure and syntactic functions of the past tense verb in Arabic and Uzbek languages. The study contrasts the Arabic form al-fi‘l al-māḍī, characterized by its fusional system that combines person, number, and gender, with the agglutinative affixal model of Uzbek. The findings reveal that Arabic, as a verb-centered syntactic system, employs the past tense form extensively in the functions of predicate, adverbial modifier, and attribute. In contrast, the Uzbek past tense verb predominantly functions together with participial forms, where word order plays a decisive role. These results form a scientific basis for translation practice and language teaching methodology.